Synthesis of zeolite A from bentonite via hydrothermal method: The case of different base solution - S. Srilai; W. Tanwongwan; K. Onpecth; T. Wongkitikun; K. Panpiemrasda; G. Panomsuwan; A. Eiad-ua (My University, 2020)
Zeolite A was successfully synthesized from bentonite clay using two-step hydrothermal method. The first step of hydrothermal process was performed at high temperature for short time to form hydrous sodium aluminosilicate while the second step was done at low temperature for long time to form aluminosilicate gel and eventually obtain zeolite A. In this work, various types of base solutions, including sodium hydroxide (NaOH), potassium hydroxide (KOH), sodium carbonate (Na2CO3), and potassium carbonate (K2CO3) were used to synthesize zeolite A. The zeolite A was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FT-IR). The optimum conditions for achieving zeolite A were found to be at 200 °C for 3 h in the first step with 8 M NaOH solution and at 90 °C for 72 h in the second step with 1 M NaOH solution.
Keywords: Bentonite; Potassium hydroxide; Sodium hydroxide; Base (topology); Sodium aluminosilicate; Potassium carbonate; Hydrothermal Synthesis; Sodium carbonate; Zeolite Catalysis and Synthesis